RADIOFREQUENCY AS PAIN INTERVENTIONAL THERAPY IN NEUROLOGY - Badrul Munir; Widodo Mardi Santoso; Zamroni Afif; Shahdevi Nandar Kurniawan (Journal of Pain, Headache and Vertigo, 2020)
Radiofrequency (RF) intervention uses high frequency alternating current (AC) to inhibit and alter nociceptive pathway in various locations. Radiofrequency is divided into Continuous RF (CRF) and Pulsed RF (PRF). Continuous RF is a process in which the RF current is used to produce thermal lesions on the target nerve that will result in resistance to the afferent nociceptive pathway. PRF is a process whereby short bursts of RF are discharged toward a neural target that will produce a signal for lowering pain. PRF is a therapy of neural tissue with small neurodestructive possibility and is an alternative technique for continuing RF. RF therapy is a minimally invasive procedure that has been used for about three decades to treat various chronic pain syndromes such as trigeminal neuralgia, post herpes neuralgia, lower back pain (LBP), and complex regional pain syndromes or sympathetic reflex dystrophy. The mechanism action of the PRF involves cellular structure damage, neuronal activation, altered gene expression, a global continuation of evoked synapticÂ  activity in pain fibers through centrals and changes in synaptic strength and long-term potentiation.Â  PRF with its various characteristics has a better outcome than conventional RF.